Incidence and influencing factors of 30-day unplanned readmission in chronic heart failure patients: a systematic review and meta-analysis - Chen, Tongtong; Wang, Renxiu; Song, Hongxia (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveSystematic review and meta-analysis of the incidence and risk factors for 30-day unplanned readmissions in patients with chronic heart failure(CHF).MethodsWe searched PubMed, Embase, Web of Science, Scopus, Medline, CINAHL, and Chinese databases up to February 2025. Data were analyzed by using Stata 17.0.ResultsAmong 4,040 screened publications, 21 studies were included. The incidence of 30-day unplanned readmission in CHF patients was 17.7% (95% CI: 13.9%–21.5%). Age ≥65 years (OR = 1.35, P = 0.024), diagnosed with chronic kidney disease (CKD) (OR = 1.26, P = 0.000), diabetes (OR = 1.49, P = 0.001), atrial fibrillation (AF) (OR = 1.12, P = 0.005), coronary heart disease (CHD) (OR = 5.28, P = 0.000), cardiomyopathy (OR = 1.44, P = 0.000), NYHA class ≥Ⅲ or Ⅳ (OR = 1.64, P = 0.000), use of beta blockers (OR = 1.25, P = 0.000), loop diuretics (OR = 1.41, P = 0.004), thiazides (OR = 1.22, P = 0.000), LVEF < 40% (OR = 1.44, P = 0.000), and length of stay (LOS) (OR = 1.16, P = 0.000) were risk factors for 30-day unplanned readmission in CHF patients.ConclusionsThe incidence of 30-day unplanned readmissions in patients with CHF is moderate but concerning. Accurate identification of identified risk factors for targeted interventions to reduce the need for readmissions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024610843, PROSPERO CRD42024610843.